2011
DOI: 10.1063/1.3563076
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation: Improved coil design for deep brain investigation

Abstract: This paper reports on a design for a coil for transcranial magnetic stimulation. The design shows potential for improving the penetration depth of the magnetic field, allowing stimulation of subcortical structures within the brain. The magnetic and induced electric fields in the human head have been calculated with finite element electromagnetic modeling software and compared with empirical measurements. Results show that the coil design used gives improved penetration depth, but also indicates the likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 7 publications
0
45
0
Order By: Relevance
“…Therefore, new coil designs must be created for this purpose. Studies in human subjects 16 have found that increased localization of stimulation is usually possible at the expense of depth of penetration of the stimulating field. This is also expected to hold true for TMS coils designed for small animals.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, new coil designs must be created for this purpose. Studies in human subjects 16 have found that increased localization of stimulation is usually possible at the expense of depth of penetration of the stimulating field. This is also expected to hold true for TMS coils designed for small animals.…”
Section: Resultsmentioning
confidence: 99%
“…Although non-invasive, TMS procedures are often limited by non-focal stimulation of brain regions and low overall electric field strength. Recent advancements by Crowther et al [3,4] The present study investigates a methodical approach for designing a TMS coil for medical testing for mice on the basis of Halo coil designs. TMS coils that are currently used by other research groups for stimulation of animal brains are scaled down versions of standard TMS coils that are used for stimulation of the human brain [5].…”
Section: Introductionmentioning
confidence: 99%
“…These shields can inhibit or divert the generated magnetic field, leading to more focused stimulation and improved field penetration. Complex coil designs (Zangen et al 2005, Crowther et al 2011, Deng et al 2013 have also been developed where the rate of decay from the surface is attenuated, such that the percentage of electric field intensity is increased in deeper brain regions, relative to the maximum field at the cortex. However, experiments reveal that standard TMS coils such as the figure-of-eight coil possess the ability to affect these deeper brain regions as well (Bestmann et al 2004, Hannula et al 2010, Ferreri et al 2011.…”
Section: Introductionmentioning
confidence: 99%